Trade union merger strategies purpose, process, and performance - Undy, R. (Roger) (Oxford : Oxford University Press, 2008)
As Trades Union membership has declined, merger and amalgamation have been prominent features in strategies of revitalization. Yet, there is very little systematic, empirical research into their effects on unions or the wider union movement. This study fills this gap with an analysis of British union mergers since 1978.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Labor unions -- Mergers -- Great Britain; Labor unions -- Great Britain -- History -- 20th century